Contribution of Drosophila Climbing Assay in Studying Biology and Diseases - Fauzi, Ahmad; Ramadhan, Muhamad Justitia; Zahrah, Natasya Adiba; Karomah, Sinta; Buroidah, Hikmah; Choirunisa, Nindiana; Maghfiroh, Hidayati; Zubaidah, Siti (El-Hayah:Jurnal Biologi, 2024)
The Drosophila Climbing Assay (DCA) is an essential assay for disease and other biological studies. This systematic literature review (SLR) aims to analyze DCA's distribution, treatment, and contribution during the 21st Century. VosViewer was also involved in analyzing the bibliometric and gap analysis in related studies. By using the Scopus database and limiting document types to journal articles, a total of 183 documents have been successfully collected in this SLR. After going through a selection process based on inclusion and exclusion criteria and eligibility assessment through the PRISMA procedure, 163 articles remain that can be analyzed. Behaviour, model, activity, expression, lifespan, and disease are terms that often equate to studies involving the DCA procedure. The U.S., China, and India are the three countries that most frequently report DCA. DCA has been involved intensively in behaviour, Parkinson's, and nervous system research. The co-occurrence analysis resulted in 5 clusters, and the DCA procedure to study the impact of nutrient stress and nanoparticles resulted from the identified gap analysis.